Societal costs of ovarian cancer in a population-based cohort – a cost of illness analysis. (2nd November 2022) - Palmqvist, Charlotte; Persson, Josefine; Albertsson, Per; Dahm-Kähler, Pernilla; Johansson, Mia
Abstract: Background: The societal cost associated with ovarian cancer (OC) is not well known. Increasing costs for new treatments and/or the impact of organizational changes motivates these costs to be described and communicated. This study aims to evaluate the cost of illness of OC in a population-based cohort. Material and methods: All patients diagnosed with ovarian, fallopian tube, primary peritoneal cancer, and serous cancer of undesignated primary site (UPS) in 2011–2012 were followed for six years. Direct costs, i.e., costs for health care expenditures, were gathered from the regional healthcare database. Information on indirect costs, i.e., costs of loss of production due to sick leave, was retrieved from Statistics Sweden. Sub-group analyses were conducted regarding stage, income levels, residential area, and diagnosis. Results: The cost of illness for all stages during the six years of follow-up was €201, 086 per patient, where indirect costs constituted 43.7%. The mean cost of illness per year per patient for all stages was €33, 514. Direct costs were higher in advanced stages compared to early stages for every year from diagnosis. During the first two years, there were no differences in indirect costs between early and advanced stages. However, during the third year there was a difference with higher indirect costs in advanced stages. There was no difference in direct costs depending on income levels. Regarding residential area, there was a difference in the outpatient cost during the index and second year with higher costs when chemotherapy and follow-up were provided at county hospitals, compared to at the tertiary hospital. Conclusions: Indirect costs constituted a large part of the cost of illness over 6 years from diagnosis. This could indicate that even though treatment costs can be expected to rise with the introduction of new therapies, the societal cost may decrease when survival increase.